A review on production of biodiesel from waste cooking oils - Azizi, Muzhda; Akbari, Sweeta (International Journal of Innovative Research and Scientific Studies, 2018)
Nowadays, preservation of natural resources on earth is one of the most important concerns of humanity. In this regard, increasing the consumption of energy is one of the most critical challenges that humans are facing. Because, on the one hand, the untapped use of different sources of energy from fossil fuels can destroy this natural resource and, on the other hand, pollution from the use of these resources is a serious threat to the environment. Recent research suggests that affordable, sustainable and environmentally friendly fuels, which can be a good alternative to fossil fuels, have become more important. Therefore, biodiesel has made it possible to release less greenhouse gas emission and low toxicity emissions, which can partly meet fuel requirements and is the best alternative for petroleum diesel. In addition, the waste cooking oils are a major source of biodiesel for their essential compounds, such as glycerol. The use of waste cooking oils can reduce biodiesel production cost by 60 to 90 percent. Therefore, the main objective of this review is to study the production of biodiesel using transesterification reaction of waste cooking oil as an alternative fuel to petroleum diesel that can be used easily in diesel engines.